Living with vesico-vaginal fistula: experiences of women awaiting repairs in Ebonyi State, Nigeria - Okoye, Uzoma O.; Emma-Echiegu, Nkechi; Tanyi, Perpetua L. (Tanzania Journal of Health Research, 2014)
Vesico-vaginal fistula (VVF) is one of maternal health problems confronting public health workers in Nigeria today. Information on how women suffering from this condition cope is important in that it can inform the design and delivery of programmes and interventions to address the challenges that face victims of VVF. The objective of this study was to highlight how women living with VVF cope with the health problem in Ebonyi state, Nigeria. In-depth interviews were conducted with ten women awaiting repairs at the National Fistula Centre at Abakaliki in Nigeria. Six of the women have lived with the health problem for more than ten years. Findings show that nearly all the women attributed their health problem to supernatural causes. The women stated that they go through a lot of physical and emotional problems. Some of the ways they have devised of physically coping with the problem include bathing regularly and use of strips of old wrappers as pads. Many of them cope emotionally and financially by attending religious gatherings and having some form of income yielding business. The study recommends the need for repairs to go hand in hand with vocational training so that they will have some income yielding business after repairs.